Older breast cancer survivors may harbor hereditary cancer predisposition pathogenic variants and are at risk for clonal hematopoiesis. Issue 2 (March 2020) - Slavin, Thomas P.; Sun, Can-Lan; Chavarri-Guerra, Yanin; Sedrak, Mina S.; Katheria, Vani; Castillo, Danielle; Herzog, Josef; Dale, William; Hurria, Arti; Weitzel, Jeffrey N.
Abstract: Objective: Our goal was to identify pathogenic variants (PV) associated with germline cancer predisposition in an unselected cohort of older breast cancer survivors. Older patients with cancer may also be at higher risk for clonal hematopoiesis (CH) due to their age and chemotherapy exposure. Therefore, we also explored the prevalence of PVs suggestive of CH. Methods: We evaluated 44 older adults (65 years or older) diagnosed with breast cancer who survived at least two years after diagnosis from a prospective study, compared to healthy controls over the age of 65 ( n = 36). DNA extracted from blood samples and a multi-gene panel test was used to evaluate for common hereditary cancer predisposition and CH PVs. Fisher's exact test was used to compare PV rates between groups. Results: Eight PVs in ATM, BRCA2 (x2), PALB2, RAD51D, BRIP1, and MUTYH (x2) were identified in 7 of 44 individuals with breast cancer (15.9%, 95% CI: 7–30%), whereas none were identified in healthy controls ( p = .01). Results remained statistically significant after removal of MUTYH carriers ( p = .045). PVs indicative of CH ( ATM, NBN, and PPM1D [x2]) were identified in three of 27 individuals with breast cancer who received chemotherapy and in one healthy control. Conclusion: Moderate-risk and later disease onset high-risk hereditary cancer predisposition PVs were statistically significantly enriched in our survivorship cohort compared to controls. Because age- and chemotherapy-related CH are more frequent in this population, care must be taken to differentiate potential CH PVs from germline cancer predisposition PVs.